Comparison of Haploidentical Hematopoietic Stem Cell Transplant With or Without Unrelated Cord Blood Infusion in Severe Aplastic Anemia: Outcomes of a Multicenter Study - Lei, Meiqing; Zhang, Yanming; Jiao, Wenjing; Li, Xiaoli; Zhou, Huifen; Wang, Qingyuan; Qiu, Huiying; Tang, Xiaowen; Han, Yue; Fu, Chengcheng; Jin, Zhengming; Chen, Suning; et al. (Frontiers in Immunology, 2022)
The purpose of this study in SAA patients was to compare the feasibility and efficacy of haploidentical hematological stem cell transplantation combined with a single unrelated cord blood (UCB) infusion (Haplo-cord-HSCT) or haplo-identical HSCT (Haplo-HSCT) alone. The five-year GVHD-free or failure-free survival (GFFS) was similar between the two groups (72.4 ± 3.4% vs. 65.4 ± 5.2%, P = 0.178), however, the five-year overall survival (OS) was more favorable in the Haplo-cord-HSCT group than that in the Haplo-HSCT group (84.0 ± 2.8% vs. 72.6 ± 4.9%, P = 0.022), as was transplantation-related mortality (16.4% vs. 27.4%, P = 0.039). Multivariate analysis showed that Haplo-cord HSCT was the only independent determinant of increased OS (P = 0.011). Explorative subgroup analysis showed that only a HLA-A allele match between UCB and the recipient was a beneficial factor for GFFS in the Haplo-cord-HSCT group (P = 0.011). In the haplo-cord with a HLA-A match (n = 139) or mismatch (n = 32) or?Haplo-HSCT groups, a haplo-cord HLA-A allele match was associated with lower I–IV and III–IV aGVHD. The haplo-cord with a HLA-A match subgroup also had higher five-year OS than Haplo-HSCT group (85.4 ± 3.0% vs. 72.6 ± 4.9%, P = 0.013), and higher five year GFFS than the Haplo-cord HLA-A allele mismatch subgroup (76.2 ± 3.6% vs. 56.3 ± 8.8%, P = 0.011). These findings suggest that coinfusion of a single UCB potentially improves survival of Haplo-HSCT in SAA patients and that a HLA-A allele matched UCB is the preferred option.